The Spanish version of the Childbirth Experience Questionnaire (CEQ-E): reliability and validity assessment. Issue 1 (December 2016) - Soriano-Vidal, F.; Oliver-Roig, A.; Cabrero-García, J.; Congost-Maestre, N.; Dencker, A.; Richart-Martínez, M.
Abstract Background The Childbirth Experience Questionnaire (CEQ) was originally designed to study women's perceptions of labour and birth. The main objective of our study was to adapt the CEQ to the Spanish context and determine its psychometric properties. This would provide an opportunity to evaluate women's experiences in order to improve evidence in the Spanish context as recommended by national guidelines. Methods The CEQ was translated into Spanish using a standard forward and back translation method (CEQ-E). A convenience sample of 364 women was recruited from 3 Spanish hospitals; all participants were able to read and write in Spanish. Mothers with high risk pregnancies or preterm deliveries were excluded from the study. A self-administered questionnaire on sociodemographic variables was completed by participants before discharge. Data on childbirth variables were obtained from maternity records. Between 1 and 3 months postpartum a postal CEQ-E questionnaire was sent. The CEQ-E structure was examined by a confirmatory factor analysis of polychoric correlations using a diagonally weighted least squares estimator. Reliability was assessed using Cronbach's alpha. Construct validity was conducted by testing differences in CEQ-E scores between known-groups (to differ on key variables). Results 226 (62.1%) of the recruited participants completed the postal questionnaire. The CEQ-E factor structure was similar to the original one. The Spanish version showed fit statistics in line with standard recommendations: CFI = 0.97; NNFI = 0.97; RMSEA = 0.066; SRMS = 0.077. The internal consistency reliability of the CEQ-E was good for the overall scale (0.88) and for all subscales (0.80, 0.90, 0.76, 0.68 for "own capacity", "professional support", "perceived safety" and "participation", respectively) and similar to the original version. Women with a labour duration ≤ 12 h, women with a labour not induced, women with a normal birth and multiparous women showed higher overall CEQ-E scores and "perceived safety" subscale scores. Women with a labour duration ≤ 12 h and those with previous experience of labour obtained higher scores for the "own capacity" and "participation" subscales. Conclusions The results of this study indicate that the CEQ-E can be considered a valid and reliable measure of women's perceptions of labour and birth in Spain.